PENGARUH Mangan (Mn) TERHADAP OKSIDASI KROMIUM TRIVALEN DAN PERTUMBUHAN Tagetes sp. - Margareta Prameswati; Sri Kasmiyati; Sucahyo Sucahyo (BERITA BIOLOGI, 2022)
Chromium can be found in 2 oxidation states, trivalent chromium (Cr3+) and hexavalent chromium (Cr6+) in environment. Trivalent chromium can be oxidized by manganese oxide to hexavalent chromium (Cr6+). The aim of the study was to determine the effect of Mn on the oxidation of Cr³⁺and plant growth of Tagetes. The study was conducted experimentally using a completely randomized design. The Tagetes plants grown in media with 2 treatment factors, namely Cr3+ (CrCl3) with 3 concentrations of 0, 100 and 500 mg/l) and Mn (MnSO4) with 4 concentrations of 0, 1, 5 and 10 mg/l. The plant growth and Cr6+ content in roots and shoots were measured to determine the effect and to detect the occurrence of Cr3+ oxidation. The addition of Mn in the media of Tagetes containing Cr3+ increased the Cr3+ oxidation process, indicated by the detection of Cr6+ in the roots and shoots of Tagetes. The highest Cr6+ content was found in the roots and shoots of Tagetes sp. treated with Cr3+ 500 mg/l and Mn 10 mg/l at 0.059 and 0.035 g/l, respectively. The interaction of Cr3+ and Mn treatments significantly affected the growth of Tagetes plants. Cr3+ and Mn at high concentrations increased plant height, root length, root and shoot dry weight. The interaction of Cr3+ and Mn at high concentrations inhibited the increase in the number of leaves of Tagetes.